Análise temporal e espacial de condenações de frangos em um matadouro-frigorífico - Giotto, Diana Bertani (2008)
This study aims to make a temporal and spatial analysis of condemnation post mortem partial and total of chickens in a slaughterhouse of Federal inspection located in the West of Santa Catarina. The data basis used in the presented study was daily register of occurrences of condemnation of chickens in the period that starts in september, 2006 and goes until august, 2007 following the criteria of sentences stetted by the Federal Inspection Service. Descriptive analysis based on measures of frequency distribution and tendency analysis through time series techniques with the use of moving average was defined to the temporal analysis of condemnations. The special analysis was accomplished trough Geographic Information System (GIS) for the store, organization and manipulation of the Federal inspection data, as well as the use of geographic coordinates (latitude and longitude) of each production s unit and the georreferenced map from the study s area to the specialization of the producers and from the pathological condemnation that has higher occurrence. The results demonstrated that the temporal analysis of the condemnation through moving average for the gathering of three to three months diminish data s dispersion in the distribution of the monthly frequency and define best the tendency of each factor of condemnation studied. In the spatial analysis, SIG allowed the specific localization from each producer, the origin of the lots slaughtered, the incidence in which the condemnation occurred in each lot, spatial localization from each condemnation, the viewing form the areas of higher concentration and intensity and also the monthly behavior that every pathology presented.